PENGARUH LIKUIDITAS DAN STRUKTUR MODAL TERHADAP RETURN SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN TBK PERIODE 2015-2020 - Andini Dwi Nawangsih; Trisa Indrawati (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2023)
This study aims to examine and analyze the effect of liquidity and capital structure on stock returns. Sampling technique used was purposive sampling and there are 14 companies as research samples with a population of 30 food and beverages company. Data analysis was performed using statistic with SPSS version 26. Based on the results of data analysis using the t test it is known that partially liquidity has no significant effect on stock returns while capital structure has a significant effect on stuck returns. And based on the F test simultaneously liquidity and capital structure have a significant effect on stock returns.